EVALUATION OF ANTIMICROBIAL AND ANALGESIC ACTIVITY OF DIPLOCYCLOS PALMATUS FRUITS ON ALBINO MICE - kishan J, Ram; ZEEYAUDDIN, KHAJA; P, VENKANNA; VEMULA, SATEESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study is preplanned to assess the antimicrobial and analgesic activity of the collected plants of Diplocyclos palmatus from Moinabad, Ranga Reddy, Telangana. Methods: In this study, D. palmatus fruits were used to gain the ethanolic extract and were tested for the phytochemical screening, antimicrobial activity using agar diffusion method against Gram-negative bacteria (Escherichia coli) and Gram-positive (Bacillus) and to compare its effect with the marketed standard streptomycin, ciprofloxacin, and analgesic activity of plant was performed by tail clip, tails immersion, and radiant heat method. Results: The maximum zone of inhibition is shown in the Gram-negative bacteria (E. coli) compared to standard and control. The ethanolic extract of D. palmatus fruits was shown analgesic activity and it was found to be more remarkable when compared to the standard aspirin and control. From the results of three different methods at different dose of ethanolic extract (100 mg/kg, 200 mg/kg, 400 mg/kg followed by 0–5 min interval up to 30 min), tail immersion method at 200 mg/kg dose of the D. palmatus fruits extract was achieved good results i.e., in 10 min (11.4 ± 1.93) and 15 min (13.4 ± 1.63). In tail clip method, 400 mg/kg dose is in 10 min (11 ± 1.67) and 15 min (10 ± 0.707) achieved best output, while same thing radiant heat method 200 mg/kg dose of the D. palmatus fruits extract is in 10 min (11.3 ± 1.67) and 15 min (14 ± 1.82) achieved outstanding results. Conclusion: The analgesic and antimicrobial activity of ethanolic extract of D. palmatus fruits are more significant compared to the other part of D. palmatus. Hence, the study concludes that the plant is having both analgesic and antimicrobial activity, and therefore, it can be used for various therapeutic purposes and further analysis.